Analisis Akuntabilitas Pengelolaan Dana Desa (Studi pada Nagari Aia Manggih periode 2018-2022) - Gusmita Sofia; Zalida Afni; Wiwik Andriani (Universitas Batanghari Jambi, 2023)
This study aims to find out and analyze how Accountability is in the management of Village Funds in Nagari Aia Manggih, Lubuk Attitudeing District, Pasaman Regency. The analytical method used is descriptive qualitative analysis by conducting in-depth and semi-structured interviews with informants, namely Nagari Wali, Nagari Secretary, Nagari Treasurer, and the general public. The results of the analysis show that the application of village fund management accountability in Nagari Aia Manggih has been running in accordance with applicable regulations. However, in implementing this accountability for village fund management, it was not followed by the high participation of the Nagari Aia Manggih community. The local government also hopes that there will be an increase in community participation so that the management of village funds can be maximized.